Sterile Water Versus Isotonic Saline Solution as Irrigation Fluid in Percutaneous Nephrolithotomy - Seyed Mohammad Kazem Aghamir; Farshid Alizadeh; Alipasha Meysamie; Shadi Assefi Rad; Ladan Edrisi (Urology Journal, 2009)
Introduction: We evaluated the safety of sterile water as an irrigation solution for percutaneous nephrolithotomy (PCNL). Materials and Methods: Forty-four patients with kidney calculi were enrolled in this study and randomly divided into two groups for PCNL. Approaches to the calculi were through a single subcostal access with an Amplatz sheath, and either sterile water or isotonic saline solution was used as the irrigation fluid. Serum hemoglobin, haptoglobin, sodium, potassium, and creatinine were measured before and 12 hours after the procedure. The patients were evaluated for signs of transurethral resection of the prostate syndrome during the operation for 24 hours afterwards. Results: The mean calculus size, irrigation volume, irrigation time, and age were not significantly different between the two groups. Hemolysis occurred in 10 and 9 patients in sterile water and saline groups, respectively. The mean change in haptoglobin level was -1.7 ± 59 mg/dL in the sterile water and 11 ± 55 mg/dL in the saline group. Also, the mean change in plasma sodium level was -2.2 ± 4.7 and -0.4 ± 3.8 in sterile water and saline groups, respectively. None of these values were significantly different between the two groups, nor were other laboratory values. None of the patients developed transurethral resection of the prostate syndrome or needed transfusion. Conclusion: Sterile water is an inexpensive alternative to isotonic saline for irrigation during PCNL. We did not find any difference between the two irrigation solutions regarding the safety; however, this should be confirmed further, especially for larger calculi.